Analisis aspek hukum studi kelayakan bisnis: BMT Sarana Wiraswasta Muslim Malang - Wardana, Ahmat Alfian; Emiliani, Emiliani; S, Fara Kurnia Tri; Solekah, Nihayatu Aslamatis (Maliki Interdisciplinary Journal, 2024)
The BMT Sarana Entrepreneurial Muslim Cooperative or better known as BMT SWM is one of the best BMT-based multi-business cooperatives in Malang City. The legal aspect is very important in carrying out a business feasibility study because every business carried out if there is no legal registration or registration is considered an illegal business and will be subject to sanctions. So BMT is supported by Law No. 17 of 2012 concerning cooperatives and already has NIB (Business Identification Number), NPWP (Taxpayer Identification Number), Certificate, TDP Letter (Company Registration Certificate), SIUP (Trade Business License), and HO (Disorder Permit) which supports the legal aspect.